The contributions of a hispanic immigrant home reading practices to a child’s bilingual reading development - López-Velásquez, Ángela María (Colombian Applied Linguistics Journal, 2009)
The characteristics of the Spanish home reading practices of a US immigrant Hispanic household are studied highlighting the many connections existing between the reading practices at home and at school. This longitudinal study explores how the home and school L1 reading instruction contributed to a first-grader’s initial steps towards reading in English or biliteracy. Details of Natalia´s reading in Spanish at home and at school are presented and the relationships between the reading practices in both contexts are documented.The findings in this study remind us of the importance of strong native language literacy foundations and of the role that both home and school play in fostering high literacy levels among children.